Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa pada Materi Ekosistem Siswa Kelas X SMA Negri 2 Gowa - Dzul Fahmi; Hilmi Hambali; Muh Wajdi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the influence of the Problem Based Learning Model on Students' Critical Thinking Ability on Ecosystem Material for Class X Students of State High School 2 Gowa. This type of research uses a quasi-experimental type of research or also called quasi-experiment with a